2016
DOI: 10.1073/pnas.1607728113
|View full text |Cite
|
Sign up to set email alerts
|

PDE1C deficiency antagonizes pathological cardiac remodeling and dysfunction

Abstract: Cyclic nucleotide phosphodiesterase 1C (PDE1C) represents a major phosphodiesterase activity in human myocardium, but its function in the heart remains unknown. Using genetic and pharmacological approaches, we studied the expression, regulation, function, and underlying mechanisms of PDE1C in the pathogenesis of cardiac remodeling and dysfunction. PDE1C expression is up-regulated in mouse and human failing hearts and is highly expressed in cardiac myocytes but not in fibroblasts. In adult mouse cardiac myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 46 publications
(52 reference statements)
7
94
0
Order By: Relevance
“…Among them, PDE1A and PDE1C but not PDE1B are expressed in the mouse heart [12]. Indeed, we found that Ang II infusion increased PDE1A and PDE1C expression (Online Resource 4a, b) and PDE1 activity (Online Resource 4c) in the heart, consistent with previously reported upregulation of PDE1A and PDE1C mRNA and/or protein in rodent and human hearts under pathological remodeling [12, 13, 17]. PDE1 family members are Ca 2+ /CaM-stimulated PDEs, and we have previously shown that PDE1 is responsible for Ang II-mediated reduction of cGMP in cardiomyocytes as assessed by using the PDE1-selective inhibitor IC86340 [12, 13].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Among them, PDE1A and PDE1C but not PDE1B are expressed in the mouse heart [12]. Indeed, we found that Ang II infusion increased PDE1A and PDE1C expression (Online Resource 4a, b) and PDE1 activity (Online Resource 4c) in the heart, consistent with previously reported upregulation of PDE1A and PDE1C mRNA and/or protein in rodent and human hearts under pathological remodeling [12, 13, 17]. PDE1 family members are Ca 2+ /CaM-stimulated PDEs, and we have previously shown that PDE1 is responsible for Ang II-mediated reduction of cGMP in cardiomyocytes as assessed by using the PDE1-selective inhibitor IC86340 [12, 13].…”
Section: Resultssupporting
confidence: 88%
“…Interestingly, the effects of vinpocetine on inhibiting cardiac fibroblast activation and matrix protein expression were also independent on Smad2/3 phosphorylation/activation (data not shown), which is consistent with the previous result from PDE1-selective inhibitor IC86340 [13]. Recently, we also reported the role of PDE1C deficiency in antagonizing pathological remodeling induced by thoracic aortic constriction (TAC) [17]. In the current study, we further showed that, when PDE1 activity was inhibited by the selective inhibitor IC86340, vinpocetine exhibited no additional effects on cardiomyocytes hypertrophy (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In neonatal cardiomyocytes, agents such as the alpha-adrenergic receptor agonist phenylephrine (PE) induce a 50-100% in increase in cell area 21,22 , whereas the response in adult cardiomyocytes is typically only 10-30% 21,23,24 . Therefore, we investigated the response of hiPSC-CMs to PE.…”
Section: Maturation Methods Allow An Adult Like Hypertrophic Responsementioning
confidence: 99%
“…Phosphodiesterase 1C mRNA and protein are raised in failing mouse and human hearts [61]. Likewise, PDE1A protein expression is increased by AngII and the β-AR agonist isoprenaline (ISO) in isolated cardiomyocytes, as well as following pressure overload (i.e.…”
Section: Heart Failure Pathophysiologymentioning
confidence: 99%